Moksibusi sebagai Terapi Lowback Pain Masa Nifas dalam Pelayanan Nonfarmakologis Kebidanan - Norma Mardiani; Pearly Otis PO (Jurnal Kesehatan Pertiwi, 2021)
Introduction: Complementer therapy is the phenomenon for this moment, between the another convensional therapy phenomenon, likes herbal therapy. Moksibusi therapy can get application in midwifery care are prenatal, intranatal and postnatal as midwifery nonfarmacologiest. Purpose: This research to know moksibusi effect forlowback pain. Methods: Design of reseach used experiment with one group, pre and posttest. Smpling Technic with purposive sampling 15 respondent. Data analysis used univariate and bivariate with T test. Result: Beside the result is postnatal with lowback pain 8 (53.3%) low category, 2 (13.3%) heavy category. Post test result with 7 (46.7%) respondent is low category and heavy category is 2 (13.3%). The analysis of bivariate is 0.002 (p<0.05). There is therapy effect before and after moksibusi therapy to respondent. This researched for therapy alternative, another reference with a lot of complementer method nonfarmacology therapy in midwifery care.